2022
DOI: 10.3390/ijms232012684
|View full text |Cite
|
Sign up to set email alerts
|

Promoter of Vegetable Soybean GmTIP1;6 Responds to Diverse Abiotic Stresses and Hormone Signals in Transgenic Arabidopsis

Abstract: Tonoplast intrinsic proteins (TIPs), a sub-family of aquaporins (AQPs), are known to play important roles in plant abiotic stress responses. However, evidence for the promoters of TIPs involvement in abiotic stress processes remains scarce. In this study, the promoter of the vegetable soybean GmTIP1;6 gene, which had the highest similarity to TIP1-type AQPs from other plants, was cloned. Expression pattern analyses indicated that the GmTIP1;6 gene was dramatically induced by drought, salt, abscisic acid (ABA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…MeJA-responsive is common in the plant pathogen interaction genes promoters, has been demonstrated to improve plant resistance to environmental stresses by activate defense mechanisms(Zheng et al 2011;Su et al 2011;Li et al 2021). MeJA treatment produced a signi cant induction effect on the promoter of the vegetable soybean GmTIP1;6 gene and enhanced the activity of the GUS(Feng et al 2022), and the induction of MeJA also found in AtPROPEPs and AtPEPR promoter from Arabidopsis thaliana (Safaeizadeh M, Boller T 2019). Similar results were also found in this study, the GUS activity of Pq3-O-UGT2 promoter deletion fragments can be enhanced by 48 hours of MeJA treatment, and the signi cate change is P-1399::GUS with 2.12 times increased, much more than the other six 5′ terminal series deleted fragments.…”
mentioning
confidence: 99%
“…MeJA-responsive is common in the plant pathogen interaction genes promoters, has been demonstrated to improve plant resistance to environmental stresses by activate defense mechanisms(Zheng et al 2011;Su et al 2011;Li et al 2021). MeJA treatment produced a signi cant induction effect on the promoter of the vegetable soybean GmTIP1;6 gene and enhanced the activity of the GUS(Feng et al 2022), and the induction of MeJA also found in AtPROPEPs and AtPEPR promoter from Arabidopsis thaliana (Safaeizadeh M, Boller T 2019). Similar results were also found in this study, the GUS activity of Pq3-O-UGT2 promoter deletion fragments can be enhanced by 48 hours of MeJA treatment, and the signi cate change is P-1399::GUS with 2.12 times increased, much more than the other six 5′ terminal series deleted fragments.…”
mentioning
confidence: 99%